Stretchable and Conductive Cellulose/Conductive Polymer Composite Films for On-Skin Strain Sensors - Han, Joo Won; Park, Jihyun; Ha Kim, Jung; Entifar, Siti Aisyah Nurmaulia; Prameswati, Ajeng; Wibowo, Anky Fitrian; Kim, Soyeon; Lim, Dong Chan; Lee, Jonghee; Moon, Myoung-Woon; Kim, Min-Seok; Kim, Yong Hyun (MDPI Open Access Publishing, 2022)
Conductive composite materials have attracted considerable interest of researchers for application in stretchable sensors for wearable health monitoring. In this study, highly stretchable and conductive composite films based on carboxymethyl cellulose (CMC)-poly (3,4-ethylenedioxythiopehe):poly (styrenesulfonate) (PEDOT:PSS) (CMC-PEDOT:PSS) were fabricated. The composite films achieved excellent electrical and mechanical properties by optimizing the lab-synthesized PEDOT:PSS, dimethyl sulfoxide, and glycerol content in the CMC matrix. The optimized composite film exhibited a small increase of only 1.25-fold in relative resistance under 100% strain. The CMC-PEDOT:PSS composite film exhibited outstanding mechanical properties under cyclic tape attachment/detachment, bending, and stretching/releasing tests. The small changes in the relative resistance of the films under mechanical deformation indicated excellent electrical contacts between the conductive PEDOT:PSS in the CMC matrix, and strong bonding strength between CMC and PEDOT:PSS. We fabricated highly stretchable and conformable on-skin sensors based on conductive and stretchable CMC-PEDOT:PSS composite films, which can sensitively monitor subtle bio-signals and human motions such as respiratory humidity, drinking water, speaking, skin touching, skin wrinkling, and finger bending. Because of the outstanding electrical properties of the films, the on-skin sensors can operate with a low power consumption of only a few microwatts. Our approach paves the way for the realization of low-power-consumption stretchable electronics using highly stretchable CMC-PEDOT:PSS composite films.